2019
DOI: 10.2478/ace-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Rework in Construction Projects in Ukraine

Abstract: The collapse of the Soviet Union was the cause of a significant decline in many economies of the newly created countries. However, many of them, including the Ukrainian economy, are slowly recovering. One of the largest branches of the economy in this country is construction, which, despite political turmoil, is constantly growing, especially in the private real estate development sector. Despite the fact that the construction market is constantly developing, it is limited by the costs of rework and alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Furthermore, the experts' remarks suggest that this is a major problem in Ghana's construction industry as a whole, not just in the power sector. Quite different from past research, owner-related financial concerns are seen as a significant driver of design change, but they are not the major cause [25]. This may be attributed to differences in the discipline and region of research.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the experts' remarks suggest that this is a major problem in Ghana's construction industry as a whole, not just in the power sector. Quite different from past research, owner-related financial concerns are seen as a significant driver of design change, but they are not the major cause [25]. This may be attributed to differences in the discipline and region of research.…”
Section: Discussionmentioning
confidence: 87%
“…Design changes mainly originate from the owner side and are important causative factors to time and cost overruns [24]. In another study, poor working drawings and a lack of coordination among design documents were the leading causes of variation, also describing errors in design calculations and erroneous specification descriptions as two examples of design errors that resulted in variance [25]. Owner design changes during construction were identified as the most important cause generating delays in building projects in Egypt by the questioned owners, consultants, managers, engineers, and contractors, with a relative importance index value of 76.769%.…”
Section: Causes Of Design Changementioning
confidence: 99%
See 1 more Smart Citation
“…From the studies, it is found that rework causes can be divided to client related factors [9][10][11][12][13][14], design-related factor [10-11, 14, 16-17], subcontractor [9][10][11][18][19] and site management [6, 10-11, 14, 16, 19]. All listed causes were then used in the questionnaire survey in order to know the causes of rework in infrastructure project in Pulau Pinang.…”
Section: Methodsmentioning
confidence: 99%
“…However, a study conducted by Trach et al [13] stated that excessive workload and market conditions are external factors that contribute to the level of rework in the construction project. Restrictions on access for eligible skilled and knowledgeable subcontractors and employees cause increased defects and poor workmanship.…”
Section: Subcontractor Factorsmentioning
confidence: 99%